2019
DOI: 10.1136/rapm-2018-100355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the iPACK block injectate spread: a cadaveric study

Abstract: Background and objectivesUltrasound-guided infiltration of the interspace between the popliteal artery and capsule of the knee (iPACK) block, a new regional analgesic technique, is believed to relieve posterior knee pain, after total knee arthroplasty, by targeting the articular branches innervating posterior aspect of the joint. The extent of injectate spread and the number of articular branches affected is currently unknown. This cadaveric study aimed to compare the area of dye spread and frequency of articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 13 publications
0
44
0
5
Order By: Relevance
“…In the previous literature, Runge et al reported extensive dye injectate spread into the popliteal fossa using a distal ACB 12. Similar results were reported using the IPACK block,27 suggesting supplementation of a distal ACB with an IPACK block may be redundant. However, the proximal adductor canal injection, used in the current study, captured posteromedial branch of NVM and SMGN with minimal spread into the popliteal fossa, with the exception of one specimen.…”
Section: Discussionmentioning
confidence: 75%
“…In the previous literature, Runge et al reported extensive dye injectate spread into the popliteal fossa using a distal ACB 12. Similar results were reported using the IPACK block,27 suggesting supplementation of a distal ACB with an IPACK block may be redundant. However, the proximal adductor canal injection, used in the current study, captured posteromedial branch of NVM and SMGN with minimal spread into the popliteal fossa, with the exception of one specimen.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, the proximal iPACK block resulted in a significantly greater number of patients with posterior knee pain, possibly due to differences in local anesthetic distribution between the techniques. In the proximal iPACK block, local anesthetic is injected at the femoral shaft level, just above the femoral condyle and the upper border of the posterior capsule of the knee, resulting mainly in the spread of the local anesthetic to the superior medial and lateral genicular nerves (the terminal branches of the femoral and common peroneal nerves) that run along both the medial and lateral sides of the distal femur rather than dissipating to the branches of the sciatic nerve or popliteal plexus 26–28. Therefore, the improvement in postoperative analgesia with the addition of the proximal iPACK block to ACB in previous studies might possibly be due to a synergistic blockade of the sensory innervation of the anteromedial and lateral aspects of the knee, since pain related to different parts of the knee was not observed in these studies 18–20 28.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank Tran et al 1 for their work bringing further knowledge on the spread pattern and nerve branches covered by infiltration between popliteal artery and capsule of the knee (IPACK) block.…”
mentioning
confidence: 99%